Put PEP in your step with a Podiatric Enhanced Recovery After Surgery Protocol in the outpatient adult population: a best practice implementation project. Issue 1 (9th March 2021) - Noble, Kim A.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objective: The goal of this implementation project was to improve postoperative outcomes in the Day Surgery Podiatric patient population with the implementation of an enhanced recovery after surgery (ERAS) protocol at a large urban health system in the northeastern United States. We aimed to improve postoperative patient pain scores and reduce patient length of stay (LOS) with the implementation of the podiatric ERAS protocol (PEP). Introduction: ERAS provides an evidence-based interdisciplinary approach to the preparation and care of surgical patients. The core goals of ERAS promote accelerated patient recovery after surgery by incorporating broad patient education with strategies to reduce the physiologic stress associated with surgery and anesthesia. This strategy has been applied to many major surgical specialties but has not been established in podiatric patients. Methods: The PEP evidence implementation initiative integrates two Joanna Briggs Institute tools: the Getting Research into Practice audit and feedback tool, and Practical Application of Clinical Evidence System, by incorporating proactive planning and data analyses. Baseline electronic health record data were collected in July 2019, followed by interdisciplinary PEP review, revision, implementation, and three data collection cycles. Strategic education was provided to stakeholders throughout data collection cycles. Results: This use of ERAS in the outpatient podiatric surgery population demonstrated excellence in compliance with best practice recommendations. The proactive multimodal approach of PEP revealed improvement in four measures of patient pain, with improvement from 83 to 100% of patients having a pain goal higher than their admission postoperative pain score. Patient pain goal greater than discharge pain score was also found but not sustained. Baseline data collection established that 29% of podiatric patients had a LOS less than 90 min, which improved to 42% with PEP. This finding was also not sustained in the third cycle of audit data. Missing data may have influenced these results, reinforcing the need for further study. Conclusion: The use of ERAS in orthopedic patients has an established empirical basis for use, demonstrating a reduction in both postoperative pain and LOS. This novel use of ERAS in a podiatric surgery outpatient population has similar findings but was not sustained in all audit criteria. PEP demonstrated promising reductions in postoperative pain and LOS; however, further implementation replication is needed to confirm this expansion of ERAS and the promising results.